Spatial distribution of disseminated histoplasmosis and AIDS co-infection in an endemic area of Northeastern Brazil - Francisco Gustavo Silveira Correia; Carlos Henrique Alencar; Lisandra Serra Damasceno; Isadora Cavalcanti Ramos; Lícia Borges Pontes; Terezinha do Menino Jesus Silva Leitão (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: INTRODUCTION: The spatial distribution of disseminated histoplasmosis (DH) and acquired immunodeficiency syndrome (AIDS) co-infection in adult residents of Fortaleza, Ceará, Brazil was evaluated. METHODS: Socio-demographic data for the DH/AIDS cases were obtained from a reference hospital, and socio-environmental indicators were obtained from an official Brazilian institute. Kernel analysis and local indicators of spatial autocorrelation (LISA) cluster maps were used to estimate the case density within the city. RESULTS: DH/AIDS cases were concentrated in the Northwestern and Southwestern peripheral areas of the city, related with low human development indices, but different from AIDS cases distribution. CONCLUSION: Risk factors other than AIDS infection must affect histoplasmosis development in this area.